Mycosis Fungoides Presenting as a Pigmented Purpuric Dermatosis in a Renal Transplanted Patient - João Borges da Costa; Luís Soares-Almeida; José Guerra (Journal of Organ Transplantation, 2017)
Cutaneous lymphoma after organ transplantation is rare and its diagnosis may be delayed by both atypical clinical manifestations and failure to consider it in the differential diagnosis. Beside skin-directed therapy for the stage, immunosuppression reduction is also important for disease control. We describe a clinical case of mycosis fungoides after renal transplantation and discuss the therapeutic options.
Keywords: Mycosis Fungoides